2010
DOI: 10.3892/mmr_00000295
|View full text |Cite
|
Sign up to set email alerts
|

The functional role of dendritic cells in atherogenesis (Review)

Abstract: Abstract. accumulating evidence suggests that dendritic cells (dcs) play a crucial role in the generation and progression of atherosclerosis (ATS), a lipid-related immuno-inflammatory disease. dcs have the ability to process and present antigens (mainly oxidized low-density lipoproteins, heat shock proteins and fragments of necrotic or apoptotic cells) to naïve T cells, and the activation of T cells is a key step for the progression of atherosclerotic disease. The existence of some distinct dc subtypes has now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…A possible role of these cells in the development of atherosclerosis has been of a particular interest. For example, it has been shown that statins can exert their ability to inhibit atherosclerosis by affecting the dendritic cell subpopulations [16]. In our study Roquefort cheese feeding decreased the recruitment of “myeloid” dendritic cells, while some increase in recruitment was observed for plasmacytoid dendritic cells.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…A possible role of these cells in the development of atherosclerosis has been of a particular interest. For example, it has been shown that statins can exert their ability to inhibit atherosclerosis by affecting the dendritic cell subpopulations [16]. In our study Roquefort cheese feeding decreased the recruitment of “myeloid” dendritic cells, while some increase in recruitment was observed for plasmacytoid dendritic cells.…”
Section: Discussionsupporting
confidence: 52%
“…Depending on CD8 expression two major DC populations are traditionally referred to as myeloid (CD11c + CD8 − ) and plasmocytoid (CD11c + CD86 + ) dendritic cells [16]. As shown in Figure 4, LPS stimulation in the absence of Roquefort feeding results in a pronounced increase in myeloid dendritic cells expressing CD86.…”
Section: Resultsmentioning
confidence: 99%